The Variability of Risk Factors of Slowing the Financing of Agricultural Enterprises in Ukraine - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Demchenko, Ivan; Демченко, Іван Володимирович; Демченко, Иван Владимирович; Ternovsky, Volodymyr; Терновський, Володимир Олександрович; Терновский, Владимир Александрович; Golub, Natalia; Голуб, Наталя Олександрівна; Голуб, Наталья Александровна; et al. (My University, 2016)
EN: The article deals with the theoretical aspects of the distribution the formation sources of property assets component of farm property, including real possibilities, time limits, forms and methods of financial resources. The variability of factors that covers all possible risks of financing the economic activity was determined. A systematic approach to the evaluation of the dynamic trend that slows financing risk, taking into account indicators of sustainable financial condition of agricultural enterprises was proposed. UK: У статті розглянуто теоретичні аспекти розподілу джерел формування вартісної складової майнових активів сільськогосподарських підприємств, враховуючи реальні можливості, часові обмеження, форми і методи використання фінансових ресурсів. Визначено варіацію чинників, які охоплюють всі можливі ризики фінансування господарської діяльності. Запропоновано системний підхід до оцінювання динамічного тренду, що уповільнює ризик фінансування з урахуванням індикаторів стійкого фінансового стану сільськогосподарських підприємств. RU: В статье рассмотрены теоретические аспекты распределения источников формирования стоимостной составляющей имущественных активов сельскохозяйственных предприятий, учитывая реальные возможности, временные ограничения, формы и методы использования финансовых ресурсов. Определена вариация факторов, которые охватывают все возможные риски финансирования хозяйственной деятельности. Предложен системный подход к оценке динамического тренда, что замедляет риск финансирования с учетом индикаторов устойчивого финансового состояния сельскохозяйственных предприятий.
Keywords: the variability of risk factors; nancial resources; formation sources of property assets; agricultural enterprises; варіабельність факторів ризику; фінансові ресурси; джерела формування майнових активів; сільськогосподарські підприємства; вариабельность факторов риска; финансовые ресурсы; источники формирования имущественных активов; сельскохозяйственные предприятия